Beyond millijoules: a six-dimensional tissue-dose model for fractional ablative carbon dioxide laser therapy - Stefan Bigge (International Journal of Research in Dermatology, 2026)
Fractional ablative carbon dioxide (CO2) laser treatment is commonly documented with displayed parameters such as pulse energy, power, pulse duration, density level and number of passes. These settings are device-specific inputs, not a portable description of the tissue dose. This perspective proposes a six-dimensional tissue-dose model that represents treatment as a state vector comprising ablation geometry, coagulation geometry, treated fraction, spatial distribution, heat accumulation and healing reserve. The framework was developed through a targeted narrative synthesis of foundational fractional photothermolysis studies, histologic and computational dosimetry work, wound-healing investigations, clinical consensus statements and complication literature. A targeted PubMed, Crossref, journal-archive and web search through 19 August 2026 did not identify a previously published framework integrating the same six dimensions. The model separates the delivered tissue insult from device settings and treats healing reserve as a biological and anatomical constraint on the acceptable exposure. It explains why equal millijoules, equal nominal density or equal total energy can produce different lesion geometry, local overlap, thermal burden and recovery. The framework is intended for treatment planning, cross-platform reporting, education and prospective data collection; it is not a validated dose calculator and does not support universal presets. Validation should combine expert content assessment, platform-specific histology or optical imaging, a common clinical data dictionary and prospective prediction of efficacy, delayed healing, postinflammatory hyperpigmentation and scarring. A shared six-dimensional vocabulary may improve reproducibility while preserving the site-and patient-specific judgment required for safe fractional ablative laser therapy.